Effectiveness of Scotland's National Naloxone Programme for reducing opioid‐related deaths: a before (2006–10) versus after (2011–13) comparison. (4th February 2016) - Bird, Sheila M.; McAuley, Andrew; Perry, Samantha; Hunter, Carole
Abstract: Aims: To assess the effectiveness for Scotland's National Naloxone Programme (NNP) by comparison between 2006–10 (before) and 2011–13 (after NNP started in January 2011) and to assess cost‐effectiveness. Design: This was a pre–post evaluation of a national policy. Cost‐effectiveness was assessed by prescription costs against life‐years gained per opioid‐related death (ORD) averted. Setting: Scotland, in community settings and all prisons. Intervention: Brief training and standardized naloxone supply became available to individuals at risk of opioid overdose. Measurements: ORDs as identified by National Records of Scotland. Look‐back determined the proportion of ORDs who, in the 4 weeks before ORD, had been (i) released from prison (primary outcome) and (ii) released from prison or discharged from hospital (secondary). We report 95% confidence intervals for effectiveness in reducing the primary (and secondary) outcome in 2011–13 versus 2006–10. Prescription costs were assessed against 1 or 10 life‐years gained per averted ORD. Findings: In 2006–10, 9.8% of ORDs (193 of 1970) were in people released from prison within 4 weeks of death, whereas only 6.3% of ORDs in 2011–13 followed prison release (76 of 1212, P  < 0.001; this represented a difference of 3.5% [95% confidence interval (CI) = 1.6–5.4%)]. This reduction in the proportion of prison release ORDs translates into 42 fewer prison release ORDs (95% CI = 19–65) during 2011–13, when 12 000 naloxone kits were issued at current prescription cost of £225 000. Scotland's secondary outcome reduced from 19.0 to 14.9%, a difference of 4.1% (95% CI = 1.4–6.7%). Conclusions: Scotland's National Naloxone Programme, which started in 2011, was associated with a 36% reduction in the proportion of opioid‐related deaths that occurred in the 4 weeks following release from prison.